Dynamics of oral microbiome acquisition in healthy infants: A pilot study - Li, Yihong; Saraithong, Prakaimuk; Zhang, Lanxin; Dills, Ashley; Paster, Bruce J.; Xiao, Jin; Wu, Tong Tong; Jones, Zachary (Frontiers in Oral Health, 2023)
The human oral microbiota is one of the most complex bacterial communities in the human body. However, how newborns initially acquire these bacteria remains largely unknown. In this study, we examined the dynamics of oral microbial communities in healthy infants and investigated the influence of the maternal oral microbiota on the acquisition of the infant’s oral microbiota. We hypothesized that the infant oral microbial diversity increases with age. One hundred and sixteen whole-salivary samples were collected from 32 healthy infants and their biological mothers during postpartum and 9- and 15-month well-infant visits. Bacterial genomic DNA was extracted and sequenced by Human Oral Microbe Identification using Next Generation Sequencing (HOMINGS) methods. The Shannon index was used to measure the microbial diversity of the infant-mother dyads (alpha diversity). The microbial diversity between the mother-infant dyads (beta-diversity) was calculated using the weighted non-phylogenetic Bray-Curtis distance in QIIME 1.9.1. Core microbiome analysis was performed using MicrobiomeAnalyst software. Linear discriminant analysis coupled with effect size analysis was used to identify differentially abundant features between mother and infant dyads. A total of 6,870,571 16S rRNA reads were generated from paired mother–infant saliva samples. Overall, oral microbial profiles significantly differed between the mother and infant groups (p<0.001). The diversity of the salivary microbiomes in the infants increased in an age-dependent manner, whereas the core microbiome of the mothers remained relatively stable during the study period. Breastfeeding and gender did not affect the microbial diversity in infants. Moreover, infants had a greater relative abundance of Firmicutes and a lower abundance of Actinobacteria, Bacteroidetes, Fusobacteria, and Proteobacteria than their mothers. The SparCC correlation analysis demonstrated constant changes in infants' oral microbial community network (p<0.05). This study provides new evidence that the oral cavities of infants are colonized by a distinct group of bacterial species at birth. The acquisition and diversity of changes in oral microbial composition are dynamic during the first year of an infant’s life. Before reaching the second birthday, the composition of the oral microbial community could be more similar to that of their biological mothers.